Transformation of spatial pattern and declining of social capital in Dhaka city , Bangladesh - Munni, Sheikh Rubaiya Sultana (BRAC University, 2011)
In human settlement, there is a strong link between spatial quality and societal values. A space has two facts: physical phenomenon and a mental arena. Both of them are influenced by the social process (Sheikh, 2006). Nowadays in our country, we are experiencing rapid unplanned urbanization due to the pressure of huge population and globalization. In course of time urban areas are developed for business, education, and administrative purposes. People are coming to urban area for livelihood. To accommodate the huge population, there occurs lot of changes in their living space and pattern. Our traditional living space is being demolished. In the past, people lived in horizontal space but now people are living in a tight and congested area where the traditional space is not respected. The community space, interaction spaces are very rare there. So social bonding is being destroyed. They are living like a machine which is very much contrary to our culture (Sheikh, 2006). This trend is destroying our social capital. This paper aims to study how transformation of spatial pattern affects our living style and turns our social capital (focusing on community network, trust, dependency and cooperation) towards the declination. It also aims to give some recommendations to make this transformation of spatial pattern organized and planned to prevent the declination of our social capital.